An attention-based view of short-termism: The effects of organizational structure. Issue 2 (April 2020) - Kleinknecht, Robert; Haq, Hammad Ul; Muller, Alan R.; Kraan, Karolus O.
Abstract: Debates about short-termism in business tend to center around the role of shareholder pressures and managers' incentives, while the role of organizational structure remains understudied. In our paper, we adopt an attention-based lens to elucidate the role of organizational structure in directing the attention of management towards pressures for short-term results at the expense of the long term. Specifically, we argue that greater scale of operations, hierarchy, bureaucracy, and workforce flexibility reduce slack resources available to senior managers and increase the complexity of information presented to them in different ways. As a result, the senior managers shift their attention to short-term pressures, which are more easily understood, at the expense of attention for long-term considerations. Analysis based on a survey of senior managers in 3221 private firms in the Netherlands provides support for our arguments.